2015
DOI: 10.1016/j.forsciint.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Perspective distortion in craniofacial superimposition: Logarithmic decay curves mapped mathematically and by practical experiment

Abstract: The superimposition of a face photograph with that of a skull for identification purposes necessitates the use of comparable photographic parameters between the two image acquisition sessions, so that differences in optics and consequent recording of images does not thwart the morphological analysis. Widely divergent, but published, speculations about the thresholds at which perspective distortion becomes negligible (0.5 to >13.5 m) must be resolved and perspective distortion (PD) relationships quantified acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 18 publications
1
56
0
Order By: Relevance
“…Stephan finds a distortion effect of ~ 5% at distances less than 2.5 m, and confirmed earlier studies that 12 m is required for photographic distortion to be negligible (< 1%) [39].…”
Section: Materials (I) Photographs Of Ms Pearce-stevenson and The Facsupporting
confidence: 82%
See 1 more Smart Citation
“…Stephan finds a distortion effect of ~ 5% at distances less than 2.5 m, and confirmed earlier studies that 12 m is required for photographic distortion to be negligible (< 1%) [39].…”
Section: Materials (I) Photographs Of Ms Pearce-stevenson and The Facsupporting
confidence: 82%
“…The foreshortening and widening of the face may also be due to photographic distortion, which causes the lower face to recede and the upper face to expand when the skull is photographed at distances of less than 2.5 m [38,39]. It also the case that errors in assigning the landmarks onto a 2D image [59] may have contributed to the resulting facial shape, and in particular at the mid-ramus and gonion.…”
Section: Discussionmentioning
confidence: 99%
“…(4a) A 179‐mm cube photographed at a distance of 0.7 m. (4b) The same cube photographed with the same camera and lens, but at a camera‐to‐subject distance of 4.0 m. (4c) Superimposition of (4a) and (4b). Panel 4 reproduced from Stephan p. 257.e4 with permission from Elsevier.…”
Section: Previously Reported Subject‐to‐camera Distances (Floor Valuementioning
confidence: 99%
“…Superimposition of the face-images and the skull-images indicated that some of the face-images may have camera distortion. Earlier research on perspective distortion 10,39 indicate that distortion is unavoidable among the face-images used in this research as it is possible that many of these face-images had been photographed with lensobject distances that are less than 12 m as facial image photography at greater than 12 m distance is indeed rare 39 . Freeform Modelling Plus allows a perspective view in order to correct for close-up images of the subject but the extent of such correction that Freeform…”
Section: Based On the Results Inmentioning
confidence: 93%